Antimicrobial Resistance in Iraq: A Public Health Emergency in the Shadow of Conflict (Razi Medical Journal, 2025)
Antimicrobial resistance (AMR) is now a serious public health issue in Iraq, with high rates of multidrug-resistant bacteria and significant mortalities associated with it in different healthcare and community settings. Key contributors include the widespread issue of easy over the counter access to antibiotics, systemic failures in antibiotic management practices and diagnostic support, and critical gaps in infection prevention and control practices. Furthermore, decades of prolonged conflict have deeply devastated the healthcare infrastructure, displaced medical professionals, and introduced unique environmental contaminants that accelerate resistance development. The absence of a strong, standardized national surveillance system further impedes understanding of the crisis's true scope and evolution. To effectively counter this multifaceted challenge, a coordinated national strategy based on the 'One Health' approach is urgently needed. Policy recommendations include strengthening health system infrastructure and capacity, strictly enforcing antibiotic prescription regulations, implementing national antibiotic management initiatives, enhancing infection prevention and control (including vaccination programs), expanding public education and awareness initiatives, and developing strong national surveillance and research systems. Ultimately, while combating AMR in Iraq requires a profound national commitment, its success equally depends on sustained international collaboration, technical aid, and financial support. International assistance extends beyond simple humanitarian aid. It represents an essential strategic necessity for global health security, unequivocally showing our collective responsibility to combat a widespread problem that threatens every corner of the world. This paper explores the main factors behind the AMR crisis in Iraq and proposes viable resolutions.
Keywords: Antimicrobial resistance; Iraq; Sensitivity; Conflict; One Health